Isotopic and elemental composition of selected types of Italian honey. (February 2017) - Bontempo, Luana; Camin, Federica; Ziller, Luca; Perini, Matteo; Nicolini, Giorgio; Larcher, Roberto
Highlights: Isotopic and elemental ranges of variability were determined in Italian honeys. Botanical variety strongly affects honey isotopic and elemental composition. Geographical origin affects honey SIRs and elements within botanical variety. Abstract: According to EU law, the country of origin in which the honey was produced must be declared on the label and the botanical origin can be indicated. Conventional honey analyses are not always applicable and effective for determining the geographical and botanical origin of honey. In this study 265 honey samples of different botanical origin (polyfloral, citrus, rhododendron, eucalyptus, acacia, chestnut and honeydew) produced throughout Italy in different years were analysed to determine stable isotope ratios (SIRs) using Isotope Ratio Mass Spectrometry and mineral element content using Inductively Coupled Plasma Optical Emission Spectroscopy. The aim was to verify the relationship between these parameters and the geographical origin of honey and the botanical species, as has already successfully taken place for other commodities. The characteristic ranges of variability in terms of SIRs and mineral content in genuine Italian honey samples are presented, as well as their compliance with AOAC limit.